2014
DOI: 10.1039/c4nr02535k
|View full text |Cite
|
Sign up to set email alerts
|

Peptide modified gold nanoparticles for improved cellular uptake, nuclear transport, and intracellular retention

Abstract: Gold nanoparticles (GNPs) are being extensively used in cancer therapeutic applications due to their ability to act both as an anticancer drug carrier in chemotherapy and as a dose enhancer in radiotherapy. The therapeutic response can be further enhanced if nanoparticles (NPs) can be effectively targeted into the nucleus. Here, we present an uptake and removal of GNPs functionalized with three peptides. The first peptide (RGD peptide) enhanced the uptake, the second peptide (NLS peptide) facilitated the nucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
124
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(126 citation statements)
references
References 43 publications
2
124
0
Order By: Relevance
“…endoplasmic reticulum, Golgi complex). 34 In order to demonstrate the feasibility of using nanoshells as a multiplex platform for cell analysis in both domains (intra and extracellular), the nanoparticle surface was functionalized with either a NLS (nuclear localization signal) peptide or an anti-IGFR antibody. The nanoshells modified with NLS peptides are expected to be internalized and localized to the nuclear membrane.…”
Section: Resultsmentioning
confidence: 99%
“…endoplasmic reticulum, Golgi complex). 34 In order to demonstrate the feasibility of using nanoshells as a multiplex platform for cell analysis in both domains (intra and extracellular), the nanoparticle surface was functionalized with either a NLS (nuclear localization signal) peptide or an anti-IGFR antibody. The nanoshells modified with NLS peptides are expected to be internalized and localized to the nuclear membrane.…”
Section: Resultsmentioning
confidence: 99%
“…Recently we have shown that complement system plays an important role in uptake and clearance of nanoparticles as well as the modulation of proinflammatory immune response (Pondman et al, 2015). Yang et al (2014) functionalized the GNPs with three different peptides including RGD peptide, NLS peptide and pentapeptide. This functionalization enhanced the uptake (RGD peptide), facilitated the nuclear delivery (NLS peptide) and covered the rest of the surface (pentapeptide) resulting in protection of the peptide-capped GNPs from the binding of serum proteins (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The dose enhancement to high-value targets, e.g., the nucleus, is expected to be higher for GNPs closer to the target and lower for GNPs farther away from the target. A recent study [25] shows that nuclear targeting with nanoparticles is achievable and could thus be employed here to maximize damage to the tumor cells DNA.…”
Section: Discussionmentioning
confidence: 99%